Chronic viral hepatitis and primary liver cancer in the republic of Sakha (Yakutia) - S. S. Sleptsova; S. S. Sleptsov; M. N. Andreev; M. E. Ignatieva; L. I. Budatsyrenova (Журнал инфектологии, 2019)
Study objective: identification of risk factors for the formation of cirrhosis and PLC in patients with chronic hepatitis B, C and D to develop a personalized, approach in treatment and prevention, of complications.Materials and. methods. The materials of the official statistics of the Office of Rospotrebnadzor in the Republic of Sakha (Yakutia), the infectious disease department for treating patients with viral hepatitis of the Yakutsk Clinical Hospital were studied. Complex clinical, serological, and. molecular biological studies with the genotyping of hepatitis B, C, and D viruses were conducted (n = 354).The results of the study. The prevalence of CVH B, C and. D in the territory of Yakutia is the primary cause of high, complications (such, as cirrhosis and. PLC) rate.The most significant risk factors for the formation of cirrhosis and. PLC in CVH among the population, living in various geographical areas of the republic are identified. Large-scale vaccination, against hepatitis B will not only significantly reduce the amount of deaths caused, by HBV infection, but also generally have a positive effect on the epidemiological situation in the region. The organizational model for assisting CVH patients in the Republic of Sakha (Yakutia) has been developed.Findings. Regions with the highest prevalence of hepatitis B, C and. D with the progressive course of the disease are identified. Risk factors for PLC in hepatitis B, C and. D are isolated.